Serenity [videorecording (Blu-Ray)] - Whedon, Joss, 1964-; Fillion, Nathan, 1971-; Tudyk, Alan; Baldwin, Adam, 1962-; Glau, Summer; Ejiofor, Chiwetel; Green, Jack N., 1946-; Newman, David, 1954- (Universal Studios Home Entertainment, 2008)
The crew of the Serenity is getting desperate. They are laying low in order to protect their doctor, Simon Tam, and his telepathic traumatized little sister, River. Simon and River are hiding from the Alliance. This has made getting jobs harder and now they are desperate. When they take River on a robbery during which the Reavers attack, Simon decides that it's time to leave the crew of the Serenity for his and River's safety. She mutters 'Miranda, ' going berserk and nearly shooting Capt. Malcolm Reynolds. Simon has to use the safety word to put her to sleep. Reynolds decides to take them back on board for safety, only now an Alliance operative is on their tracks and making Reynolds determined to find out what 'Miranda' is and what the Alliance is hiding.